Energy: Revival of a burning matter - Atanas Kolev; Armin Riess (EIB Papers, 2007)
The main purpose of this paper is to preview the other contributions to this volume of the EIB Papers. In this context, it offers a few additional perspectives. One highlights why energy issues have re-emerged as a matter of policy interest. Another concerns the difference between the macroeconomic impact of the oil price shocks of the 1970s and that of the recent rise in international energy prices. A third perspective - set against concerns about the security of energy supply for Europe - pertains to the wide variation in energy import dependency across EU countries. Lastly, the paper comments on the energy efficiency ambitions of the European Union.
Keywords: 330; Energieversorgung; EU-Staaten